Active drug loading and release behaviors of fourfold channel flopped‐ferritin variants. (13th October 2021) - Oh, Hyeok Jin; Jung, Yongwon
Abstract: Human ferritin has been heavily investigated as a protein‐based drug deliver agent, due to its unique hollow cage structure for drug loading and an intrinsic tumor targeting function. However, facile strategies for high‐level drug loading and controlled release have not been established, which hampered the use of ferritin as an in vivo delivery platform. We examined active drug uptake and release patterns of various flopped ferritin variants, which use fourfold channels as a route for drug uptake. A flopped channel pore structure was adjusted by diverse mutations around the helix‐connecting loop of the channel. Active loading and release of anti‐cancer drug doxorubicin for these ferritin variants were quantitatively monitored. Drug‐loading ability and spontaneous release degree were both enhanced by channel flopping and a pore size increase. The results could lay a stepping stone for further understanding of drug loading via fourfold ferritin channels. Abstract : Characterization of active drug uptake processes with fourfold channel flopped ferritin variants: Active drug loading and release properties of flopped ferritins were closely monitored to investigate the effects of fourfold channel structures for this attractive drug‐loading method of cage protein drug delivery vesicles.